Dimensi Fenomenologi Perkawinan Usia Muda di Malang - Mustla Sofyan Tasfiq (Universitas Wahid Hasyim Semarang, 2021)
Indonesia shows a high prevalence rate of marriage at young age or underage marriage. The number of child marriages in Indonesia from 2008 to 2018 has shown a decline. In 2008-2012, the percentage of child marriage under 18 years of age was still relatively high, namely 14.67%. Continued in 2013-2014, it decreased to 13%, and decreased in 2018 with an early marriage rate of 11.21%. Malang, East Java is an area that shows that the phenomenon of early age marriage or child marriage is still rife. Therefore, the author wants to examine how the practice of child marriage in Malang is seen from the perspective of phenomeological theory. Using qualitative methods, descriptive analysis, the data used will be data obtained from the national statistical agency, then from the religious court. Then analyzed using the phenomenological theory of Edmund Husserl. After postponing it to find out the essence behind the phenomenon of young marriage in Malang, we found several factors. socialization of children and lack of control from parents, low awareness of public education, and the community's economy. Indonesia menunjukkan angka prevelensi perkawinan usia muda atau perkawinan dibawah umur yang cukup tinggi. Angka pernikahan anak dibawah umur di Indonesia dari tahun 2008 hingga 2018 tercatat telah menunjukkan penurunan. Pada tahun 2008-2012, presentase perkawinan anak usia dibawah 18 tahun masih terbilang tinggi yakni 14,67%. Dilanjutkan pada tahun 2013-2014 turun menjadi 13%, dan semakin turun pada tahun 2018 dengan angka perkawinan dini sebanyak 11,21%. Malang Jawa Timur merupakan daerah yang menunjukkan bahwa fenomena perkawinan usia dini atau perkawinan anak masih marak terjadi. Oleh karena itu penulis ingin mengkaji bagaimana praktik perkawinan anak di daerah Malang dilihat dari perspektif teori fenomeologi. Menggunakan metode kualitatif, deskriptif analisis,maka nantinya data yang digunakan adalah data yang diperoleh dari badan statisti nasional, kemudian dari pengadilan agama. Lalu dianalisis menggunakan teori fenomenologi Edmund Husserl. Setelah dilakukan penundaan untuk mengetahui esensi yang melatarbelakangi fenomena perkawinan usia muda di Malang, maka kami menemukan beberapa faktor. pergaulan anak dan kurangnya kontrol dari orang tua, rendahnya kesadaran pendidikan masyarakat, dan ekonomi masyarakat.